(untitled) (International Journal of Current Engineering and Technology, 2014)
Soil parameters requires as inputs for various hydrological, soil erosion, biophysical and ecosystem models to estimate and forecast changes in climatic condition as well as in our future life conditions. Soil parameter of Bagmati River basin of Nepal is determined for its better management and fulfil demand of models. Soil samples (0-15cm and 15 -30 cm) depth were collected from 78 locations with 3 replicates, considering slope, aspect and land cover for analysis of texture, bulk density, organic matter content, electric conductivity and pH. These parameters were analysed using methods are sieve, core cutter, Walkley-Black wet combustion, electric conductivity meter and pH meter respectively. Saturated hydraulic conductivity was determined using double ring infiltrometer. Result reveals that soil distribution of the study area is consisted of twenty six different soil mapping units, mapping units 8 and 12 appear to be dominant in the area. Soil texture in both the depths varied from clay to sandy loam. The bulk density 1.523 g/cm-3. Similarly, organic matter content 3.29% and 2.54%, electric conductivity 4.39 and 0.485 ms/cm of surface and sub soil respectively. Surface soil was acidic but sub soil was alkaline in nature with hydraulic conductivity 28.35 mm/hr. The highest positive correlation between is BD–pH followed by BD-SHC in both layer but highest negative correlation between BD-OC followed by EC- pH and vice versa for surface and sub soil respectively.